#TITLE_ALTERNATIVE# - Irfana Perdani (NIM 155 00 009), Aulia
Abstract : Nusa Penida is known to have bright, promising future in tourism. Its Hindu temples endowed with unique architecture and beautiful landscape of white sandy beaches are highly potential tourist attractions, if only they were optimally developed. Unfortunately, the absence of crucial sea transportation in the island results in low communitys prosperity and stagnant acceleration in its development. The purpose of this thesis is to engineer the construction of ferry port in Nusa Penida, specifically focusing in the floating pier or pontoons design. Field surveys result, such as tidal height and wind speed are key input in the calculation. With least square method, tidal height data is being analysed to obtain tidal components, type and tidal elevation. Wind speed data during 15 years is being predicted by hindcasting method and wave frequency analysis to obtain design wave height and period. By Ref-dif assistance, a software to model wave refraction and diffraction behavior, we can get wave height in the shoreline. The aforementioned wave data, combined with previous hidrooceanographic datas, plus ship characteristic data are used as port designs parameters. Berthing, mooring force and pile analysis are calculated to identify the amount of forces applied to the port.